2005
DOI: 10.1298/jjpta.8.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intermittent Weight-Bearing and Clenbuterol on Disuse Atrophy of Rat Hindlimb Muscles

Abstract: Abstract. The present study was undertaken to evaluate the effects of intermittent weight-bearing (IWB) combined with β2-agonist clenbuterol (Cb) medication for suppressing muscle atrophy during progressive disuse atrophy. Male Wistar rats (age: 8weeks, body weight: 232 ± 14 g) were divided into a control group (CON) and an experimental group. The experimental group was further subdivided into a Cb medication group under normal conditions and a hindlimb unweighting (HU) treatment group. The HU treatment group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 52 publications
0
12
1
Order By: Relevance
“…The results suggest that Cb exerts anabolic effects that are load-dependent and musclespecific. Our previous study 13) also demonstrated that Cb alone could suppress a decline in muscle weight with no effect on contractility, while IWB alone suppressed a decline in muscle contractile properties but had little effect on muscle morphological characteristics. The combination of IWB and Cb was useful in suppressing atrophy in type I fiber-predominant SOL 13) .…”
mentioning
confidence: 81%
See 4 more Smart Citations
“…The results suggest that Cb exerts anabolic effects that are load-dependent and musclespecific. Our previous study 13) also demonstrated that Cb alone could suppress a decline in muscle weight with no effect on contractility, while IWB alone suppressed a decline in muscle contractile properties but had little effect on muscle morphological characteristics. The combination of IWB and Cb was useful in suppressing atrophy in type I fiber-predominant SOL 13) .…”
mentioning
confidence: 81%
“…Then the muscle was mounted onto a force-recording device (LTS-500GA, Kyowa, Japan) and bathed in Ringer's solution (25 C) which had been aerated with gas (95%O 2 / 5%CO 2 ). The muscle was stretched to 110% of its resting length and stimulated with a supramaximal square wave (0.2 ms duration) delivered via two parallel platinum electrodes using an electric stimulator (SC6, Medelec, UK) 13) . Contractile responses were recorded and analyzed on an analog-to-digital converter coupled to a computer.…”
Section: Muscle Preparation / Measurement Of Contractile Propertiesmentioning
confidence: 99%
See 3 more Smart Citations